2020
DOI: 10.1002/humu.24154
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and ES cell‐based functional evaluation of BRCA2 variants identified in families with breast cancer

Abstract: The discovery of high-risk breast cancer susceptibility genes, such as Breast cancer associated gene 1 (BRCA1) and Breast cancer associated gene 2 (BRCA2) has led to accurate identification of individuals for risk management and targeted therapy. The rapid decline in sequencing costs has tremendously increased the number of individuals who are undergoing genetic testing worldwide. However, given the significant differences in population-specific variants, interpreting the results of these tests can be challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…No significant differences in this interaction were observed compared to wild-type BRAC2, indicating that the mutation was neutral with respect to the function of the BRCA2 C-terminal RAD51-binding domain. In human BRCA2, the S3303C mutation, a mutation at the corresponding amino acid of S3323 in canine BRCA2, was also reported [ 22 ]. The S3303C mutation was reported as a functionally neutral mutation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant differences in this interaction were observed compared to wild-type BRAC2, indicating that the mutation was neutral with respect to the function of the BRCA2 C-terminal RAD51-binding domain. In human BRCA2, the S3303C mutation, a mutation at the corresponding amino acid of S3323 in canine BRCA2, was also reported [ 22 ]. The S3303C mutation was reported as a functionally neutral mutation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In human BRCA2, the S3303C mutation, a mutation at the corresponding amino acid of S3323 in canine BRCA2, was also reported [ 22 ]. The S3303C mutation was reported as a functionally neutral mutation [ 22 ]. Together with these results, the S3323N mutation is probably a neutral mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Several assays, including our mouse embryonic stem cell (mESC)-based assay, have been developed in the recent years to evaluate the functional significance of BRCA2 variants. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 Many of these assays have been used to analyze hundreds of BRCA2 variants by improving throughput and often classifying the variants using a computational model to assess the functional impact of the variants. 10 , 12 , 19 The mESC-based assay is a comprehensive assay to evaluate BRCA2 variants.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 13 In this assay, individual variants are generated by recombineering in a bacterial artificial chromosome (BAC) clone containing full-length human BRCA2 . The individual BAC clone encoding a single BRCA2 variant is then expressed in Brca2 cko/ko mESCs and examined for its ability to complement the loss of Brca2 in mESCs by assessing cell viability and sensitivity to different DNA-damaging agents 7 , 8 , 13 , 14 , 16 , 17 , 18 ( Figure 1 A). We have recently used a statistical algorithm to predict the probabilities on impact of function (PIFs) using the data from the mESC-based assay.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has explored why the FDRs of hereditary cancer patients refuse genetic testing from several perspectives. 10 , 11 Numerous studies have confirmed that genetic testing behaviours are affected by health insurance, education level, healthcare professional recommendations, health literacy and family supervision. 12 , 13 Perceived barriers to genetic testing were found to be the most important psychological factors.…”
Section: Introductionmentioning
confidence: 99%